Pengembangan LKPD Ramah Disgrafia untuk Meningkatkan Keterampilan Menulis Permulaan Siswa Kelas II Sekolah Dasar - Wigati, Farah Dwi Agustina; Istiq’faroh, Nurul; Kholifah, Siti Nur (CV. Kurnia Grup, 2026)
This research is motivated by the gap between the achievement of early writing learning and the actual abilities of elementary school students, especially students who show symptoms of dysgraphia. In addition, the lack of relevant learning media also contributes to this research. The purpose of this research is to develop dysgraphia-friendly Student Worksheets (LKPD) as a solution to overcome obstacles in early writing in elementary school students. Dysgraphia is a disorder or difficulty in writing skills characterized by illegible, disproportionate writing and weak fine motor coordination. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation and evaluation. The subjects of this study consisted of media experts and five second-grade elementary school students. Data collection techniques were carried out through observation, interviews, questionnaires and documentation. The results of the study indicate that the dysgraphia-friendly Student Worksheet has a validity level of 93.75% with a very valid category, and a practicality level of 90.7% with a very practical category. Furthermore, the implementation results showed an average student performance of 90%, categorized as very good, indicating that this media is effective in improving students' writing skills. Visual scaffolding features such as bolding (tracing) and the use of three-line guidelines have been proven to be able to assist students in independent activities. This media is able to increase learning independence and provide positive affective responses from students. Thus, the dysgraphia-friendly Student Worksheet is declared feasible, practical, and effective for use in Indonesian language learning in elementary schools.